2015
DOI: 10.1097/spv.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transobturator Midurethral Sling Placement on Urgency and Urge Incontinence

Abstract: TVT-O placement is associated with cure/improvement of U and UUI in a significant proportion of patients with mixed urinary incontinence. Further, the observed improvements in U/UUI persist at 12 months and appear to have a durable positive association with QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Other investigators have reported similar findings (28,29). Theoretically, reconstitution of the pubourethral ligament may lead to improved urethral coaptation (by stabilizing the posterior urethra) and more effective urge suppression.…”
Section: Discussionsupporting
confidence: 82%
“…Other investigators have reported similar findings (28,29). Theoretically, reconstitution of the pubourethral ligament may lead to improved urethral coaptation (by stabilizing the posterior urethra) and more effective urge suppression.…”
Section: Discussionsupporting
confidence: 82%
“…Costantini et al (31), comparing TO-TVT with RP-TVT in an RCT, determined that 31 women (66%) in the TOT group had baseline MUI and showed a patient-reported success rate of 77.4% at year 3. Habibi et al (30) also reported that patients who were cured of MUI after having incontinence surgery had higher satisfaction rates compared to those with persistent UUI. In our study, the overall satisfaction rate was significantly higher compared to those with persistent UUI at the first-and third-year follow-up (90% versus 56%, p <0.001 at year 1; 82% versus 32%, p <0.001 at year three).…”
Section: Discussionmentioning
confidence: 98%
“…Only limited studies have assessed QoL after TOT placement. Habibi et al (30) found that the beneficial effects of TVT-O placement on QoL persisted at 12 months and that the QoL measurements were correlated with urgency outcomes. In another study which evaluated the long-term effects of TOT and TVT-O on QoL, 85-87% of patients reported significant improvements in QoL (9,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that assess functional recovery after implantation of a transobturator suburethral tape are limited [4,16]. Additionally, different questionnaires are often used, making it difficult to compare the results.…”
Section: Introductionmentioning
confidence: 99%